パラカス文化期結び技法で作られた頭帯の再現 - Watanabe, Keiko (2021)
The book I am presenting, as Head of the Art and Design Academic Department, is a very valuable contribution from Keiko Watanabe to our unit, with the purpose of handing down her investigation to us, heirs to the Paracas culture: Peruvian people. It has been reviewed and contextualized in an outstanding essay by Ann Peters, expert researcher of the Paracas culture, widely acknowledged internationally. As coordinator at AXIS Arte, an interdisciplinary team for research and development, I am pleased to introduce the research article on which the work carried out with Keiko Watanabe since 2017 is based, promoting workshops on the recovery of the Paracas knotting technique in the Faculty of Art and Design. These interdisciplinary spaces have had the participation of museums’ specialists, textile conservators, and people interested in the subject; along with Yuki Seo, creating great expectations, and the urge to spread and expand the Paracas textile techniques. The participation of young artists in these workshops has to be pointed out. They utilize textile techniques for their artistic creations and have incorporated Paracas textile techniques to put forward new proposals that they promote through various exhibitions. Lastly, we express our never ending gratitude to Keiko Watanabe, for trusting us and offering us her research to be published and promoted; to Ann Peters, for her valuable introduction; to Christian Arakaki, for the editorial design; and to all who contributed with their support to accomplish this publication.